2015
DOI: 10.5551/jat.24851
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardio-ankle Vascular Index in Hyperlipidemic Patients without Diabetes or Hypertension

Abstract: The present findings demonstrated that dyslipidemia increases the CAVI values in comparison to that seen in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
1
23
0
2
Order By: Relevance
“…Furthermore, no special technique is required for the measurement of CAVI. Indeed, CAVI has been associated with a number of risk factors for cardiovascular disease and the severity of CVD 10,[12][13][14][15] . An increase in the number of risk factors for metabolic syndrome was also positively correlated with an increased CAVI, probably due to insulin resistance 16) .…”
Section: Measurement Of Cavimentioning
confidence: 99%
“…Furthermore, no special technique is required for the measurement of CAVI. Indeed, CAVI has been associated with a number of risk factors for cardiovascular disease and the severity of CVD 10,[12][13][14][15] . An increase in the number of risk factors for metabolic syndrome was also positively correlated with an increased CAVI, probably due to insulin resistance 16) .…”
Section: Measurement Of Cavimentioning
confidence: 99%
“…On the other hand, another study showed that a significant increase in CAVI was observed in patients with combined hyperlipidemia who had a low (,40 mg/dL) HDL-cholesterol level but not in patients with hypercholesterolemia alone. 40 These findings suggested that CAVI may increase when both increased LDL-cholesterol level and decreased HDL-cholesterol level were observed.…”
Section: Multiple Regression Analysis Of Various Parameters For Casmentioning
confidence: 94%
“…Different ultrasonographic methods revealed that hypertension was associated with increases in arterial stiffness, whereas investigators found a higher prevalence and severity of carotid atherosclerosis in patients with hypercholesterolemia additional to arterial stiffness change. Recently, Dobsak et al [28] reported that the cardio-ankle vascular index, a sensitive non-invasive marker of arterial stiffness and atherosclerosis, was significantly increased in normotensive patients with hyperlipidemia (primary hypercholesterolemia, combined hyperlipidemia). Furthermore, Kanaki et al [29] showed that low-dose atorvastatin treatment improved arterial stiffness and exerted a reduction on central aortic pressures in patients with mild hypertension and hypercholesterolemia [29].…”
Section: The Effect Of Arterial Hypertension and Hypercholesterolemiamentioning
confidence: 98%